Microstructural, strength, and creep characterization of Sylramic™, Sylramic™-iBN and super Sylramic™-iBN SiC fibers. Issue 9 (August 2021) - Bhatt, R.T.; Sola', F.; Evans, L.J.; Rogers, R.B; Johnson, D.F.
Abstract: The chemical composition, microstructure, strength, and thermal stability of polymer-derived Sylramic™ SiC fibers fabricated by Dow Corning and COI Ceramics, Inc., and nitrogen-treated Sylramic™ SiC fibers, referred to as Sylramic™-iBN and Super Sylramic™-iBN SiC fibers, were investigated and compared. The baseline Sylramic™ SiC fibers fabricated by both vendors as well as the nitrogen-treated Sylramic™ SiC fibers are composed mostly of β-SiC (∼97 wt%) with small amounts of TiB2 (∼2 wt%), amorphous carbon (∼1 wt%) and trace amounts of B4 C. Most of the amorphous carbon is segregated at the core/interior of the fibers. Both baseline and nitrogen-treated Sylramic™ SiC fibers have similar grain size and pore size distribution, except for a thin layer of in-situ grown crystalline BN (30–70 nm) on the surface of Sylramic™-iBN and Super Sylramic™-iBN fibers. Wide variation in strength within a batch as well as between batches is observed in both baseline and nitrogen-treated Sylramic™ SiC fibers but both types of fibers are microstructurally stable at temperatures to 1800 °C in argon and nitrogen environments compared to Nicalon™-S and Tyranno®-SA SiC fibers. Under the same creep condition, Super Sylramic™-iBN fibers show better creep resistance compared to Sylramic™, Sylramic™-iBN, Hi-Nicalon™-S, and Tyranno®-SA fibers. Possible reasons for strength variability and the mechanism of in-situ BN formation on Sylramic™ SiC fibers are discussed.